2020
DOI: 10.1016/j.ijid.2020.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and in vitro susceptibility to bedaquiline of Mycobacterium tuberculosis isolates circulating in Shaanxi, China

Abstract: The aim of this study was to investigate the molecular characteristics and in vitro susceptibility to bedaquiline of Mycobacterium tuberculosis (MTB) isolates from Shaanxi, China. Methods: The minimum inhibitory concentration (MIC) of bedaquiline was determined using the microplate alamarBlue assay for 518 MTB isolates from Shaanxi. Isolates with MIC values of bedaquiline !0.12 mg/mL were sequenced for the atpE, Rv0678, and pepQ genes. Drug susceptibility testing and spoligotyping were also conducted for all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…In this retrospective population-based study, the rate of BDQ resistance (MIC ≥ 0.25 μg/ml) among DR-TB cases without BDQ and CFZ exposure was found to be 3.1% (28/898) in Taiwan, whereas other studies found values of 1.0% in France (Veziris et al, 2017), 1.3% in Russia (Peretokina et al, 2020), 2.2-3.9% in China (Pang et al, 2017;Liu et al, 2020;Yang et al, 2020), and 2.3% in a multicountry population (Diacon et al, 2014;Pym et al, 2016;Villellas et al, 2017). Furthermore, we identified 77.3% (17/22) of MGIT-BDQ-resistant isolates harboring Rv0678 mutations (Supplementary Table S2), which might not be associated with CFZ cross-resistance (Xu et al, 2017;Ghodousi et al, 2019;Beckert et al, 2020), whereas the other studies found corresponding values of 50.0-66.7% in China (Pang et al, 2017;Yang et al, 2020), 66.7% in Australia (Martinez et al, 2018), 71.4% in Germany (Andres et al, 2020), 75.0% in France (Veziris et al, 2017), 100% in South Africa (Nimmo et al, 2020b), 100% in Russia (Zimenkov et al, 2017;Peretokina et al, 2020), and 100% in a multicountry population (Villellas et al, 2017). BDQ resistance might naturally occurred or during treatment with other anti-TB drugs (Yang et al, 2020) or previous use of antifungal drugs (Milano et al, 2009;Hartkoorn et al, 2014).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…In this retrospective population-based study, the rate of BDQ resistance (MIC ≥ 0.25 μg/ml) among DR-TB cases without BDQ and CFZ exposure was found to be 3.1% (28/898) in Taiwan, whereas other studies found values of 1.0% in France (Veziris et al, 2017), 1.3% in Russia (Peretokina et al, 2020), 2.2-3.9% in China (Pang et al, 2017;Liu et al, 2020;Yang et al, 2020), and 2.3% in a multicountry population (Diacon et al, 2014;Pym et al, 2016;Villellas et al, 2017). Furthermore, we identified 77.3% (17/22) of MGIT-BDQ-resistant isolates harboring Rv0678 mutations (Supplementary Table S2), which might not be associated with CFZ cross-resistance (Xu et al, 2017;Ghodousi et al, 2019;Beckert et al, 2020), whereas the other studies found corresponding values of 50.0-66.7% in China (Pang et al, 2017;Yang et al, 2020), 66.7% in Australia (Martinez et al, 2018), 71.4% in Germany (Andres et al, 2020), 75.0% in France (Veziris et al, 2017), 100% in South Africa (Nimmo et al, 2020b), 100% in Russia (Zimenkov et al, 2017;Peretokina et al, 2020), and 100% in a multicountry population (Villellas et al, 2017). BDQ resistance might naturally occurred or during treatment with other anti-TB drugs (Yang et al, 2020) or previous use of antifungal drugs (Milano et al, 2009;Hartkoorn et al, 2014).…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, we identified 77.3% (17/22) of MGIT-BDQ-resistant isolates harboring Rv0678 mutations (Supplementary Table S2), which might not be associated with CFZ cross-resistance (Xu et al, 2017;Ghodousi et al, 2019;Beckert et al, 2020), whereas the other studies found corresponding values of 50.0-66.7% in China (Pang et al, 2017;Yang et al, 2020), 66.7% in Australia (Martinez et al, 2018), 71.4% in Germany (Andres et al, 2020), 75.0% in France (Veziris et al, 2017), 100% in South Africa (Nimmo et al, 2020b), 100% in Russia (Zimenkov et al, 2017;Peretokina et al, 2020), and 100% in a multicountry population (Villellas et al, 2017). BDQ resistance might naturally occurred or during treatment with other anti-TB drugs (Yang et al, 2020) or previous use of antifungal drugs (Milano et al, 2009;Hartkoorn et al, 2014). In Taiwan, the 4% prevalence rate of azole-resistant Aspergillus fumigatus clinical isolates mainly emerged from the environment and during antifungal treatment (Wu et al, 2020), and its influence on BDQ resistance remains elusive.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…19 Phenotypic bedaquiline susceptibility testing found that baseline isolates had MICs at the ecological cutoff for resistance, whereas emergent bedaquiline RAVs all had MICs exceeding the threshold for phenotypic drug resistance. 20 There was no statistically significant association between low bedaquiline adherence and bedaquiline RAVs, given the small patient numbers. However, 2 patients with 100% bedaquiline adherence achieved good outcomes despite bedaquiline RAVs, whereas 5 patients with bedaquiline RAVs and suboptimal adherence all experienced unsuccessful treatment outcomes.…”
Section: Discussionmentioning
confidence: 91%